Import Regulations and the Protection of Domestic Products: An Indonesian Economic Law Perspective - Selamat Lumban Gaol; Zulfikri; Johannes Triestanto; Annisa Aminda; Raudhotul Jannah (Universitas Muhammadiyah Palu, 2026)
Import regulation is a crucial instrument within national economic policy, playing a significant role in controlling the inflow of foreign goods while safeguarding the sustainability of domestic industries. From the perspective of Indonesian economic law, import policies are not solely aimed at fulfilling domestic market demands but are also designed to maintain a balance between trade liberalization and national interests. This study seeks to examine the legal framework governing import activities as well as the various forms of protection provided to domestic products. The research employs a normative juridical method, utilizing both statutory and conceptual approaches, supported by a comprehensive review of legal literature and secondary data sources. The findings indicate that the Indonesian government has implemented a range of protective measures, including tariff-based instruments such as import duties, as well as non-tariff measures like quotas, technical standards, and the Domestic Component Level (TKDN) policy. These mechanisms are intended to strengthen the competitiveness of local industries and reduce dependency on imported goods. However, in practice, several challenges persist, including regulatory inconsistencies across sectors, weak enforcement mechanisms, and external pressures from global trade regimes that emphasize market openness. These issues highlight the need for more adaptive, integrated, and sustainable policies to ensure a proper balance between protecting domestic industries and fulfilling international trade commitments.